Cryptococcus laurentii Diarrhea in a Neoplastic Patient - Franco Calista; Federica Tomei; Pasquale Assalone; Divina Traficante; Gianni Di Pilla; Carla Pepe; Liberato Di Lullo (Case Reports in Oncological Medicine)
We present a rare case of diarrhea and neutropenia caused by Cryptococcus laurentii (C. laurentii) infection in old patient with metastatic rectal cancer who underwent FOLFOX plus Cetuximab chemotherapy. C. laurentii is an extremely rare human pathogen. To the best of our knowledge, here, we report the first case of diarrhea and neutropenia caused by C. laurentii in a 74-year-old man with metastatic rectal cancer and hepatic metastases who underwent FOLFOX plus Cetuximab chemotherapy.